Mitologiziranoto gumno vo slovenskata tradicionalna kultura - I The Mythologized Threshing Floor in Slavic Traditional Culture - I - Čausidis, Nikos (Studia mythologica Slavica, 2007)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">This work is pointed towards the semiotic and mythological aspects of the threshing floor in Slavic culture, including the period from the Middle Ages till the contemporary folklore. According to the real form and the functions of the threshing floor, its dynamical cosmological symbolic is stressed, accenting its celestial character: - threshing floor = sky/heaven; - the hinge = axis mundi; - the circular movement of the animals = cyclical dynamics of the celestial bodies. A few myths referring to this particular object are elaborated. “The threshing Floor where the Birds are threshing Immortelle” is explicitly represented in the stories from Macedonia and Bulgaria, while implicitly its presence can be noticed in the Balkan rituals connected with the “Christmas Straw” and the legends of “The Milky Way” (“Godfather`s Straw”/”Kumova slama”). The relation between the mythologized threshing floor and the faries is elaborated through the components “Fairies’ Threshing Floor” (“Vilino gumno”, “Judinsko horo”), present throughout toponyms and legends. The second part of this work will give elaboration to the motif of the “Metallic Threshing Floor”.